IN-SITU SYNTHESIS AND CHARACTERIZATION OF CHITOSAN-Fe3O4 NANOPARTICLES USING TRIPOLYPHOSPHATE/CITRATE AS CROSS-LINKER - VITA T. MARDILA; IKA O. WULANDARI; RIZKY A. SHOBIRIN; DIONYSIUS J. D. H. SANTJOJO; AKHMAD SABARUDIN (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
One pot in-situ co-precipitation of chitosan-Fe3O4 nanoparticles as a candidate of drug delivery agent have been synthesized using combination of tripolyphosphate (TPP)/citrate as cross-linkers. The aim of this study was to determine the effect of preparation process towards chitosan-Fe3O4 nanoparticles characteristics. Chitosan-Fe3O4 nanoparticles were prepared on various preparation condition including Chitosan:Fe(II):Fe(III) ratio, TPP:citrate ratio, and cross-linking time. The X-ray diffraction result shows that the phase contained in nanoparticles produced is mostly Fe3O4 phase, since the diffraction peaks of the samples were consistent with the database in crystalline pattern of the Fe3O4 phase in ICSD#26410. The percentage of Fe3O4 was obtained from Materials Analysis Using Diffraction (MAUD) program. The presence of chitosan prevents the oxidation of Fe3O4, as evidenced by larger percentage of Fe3O4 in chitosan-Fe3O4 nanoparticles than bare Fe3O4. The combination of TPP:citrate as cross-linking agent was able to produce particles with spherical shape. Cross-linking time affect the particle size, crystallite size, and percentage of Fe3O4 nanoparticles. Longer duration of cross-linking process would produce the smaller particle size and crystallite size. Meanwhile, the percentage of Fe3O4 decreased with the increasing cross-linking time, due to the oxidation of samples in contact with the oxygen dissolved in the water.